The lonely prophet : V.P. Singh, a political biography - Mustafa, Seema (New Delhi : New Age International, 1995)
Political biography of Vishwanath Pratap Singh, b. 1931, former prime minister of India.
Includes index.
Maisha
Keywords: Singh, Vishwanath Pratap, -- 1931-2008.; Prime ministers -- India -- Biography; India -- Politics and government -- 1977-